2016
DOI: 10.1063/1.4941836
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical design and fabrication of the VHF-gun, the Berkeley normal-conducting continuous-wave high-brightness electron source

Abstract: A high repetition rate, MHz-class, high-brightness electron source is a key element in future high-repetition-rate x-ray free electron laser-based light sources. The VHF-gun, a novel low frequency radio-frequency gun, is the Lawrence Berkeley National Laboratory (LBNL) response to that need. The gun design is based on a normal conducting, single cell cavity resonating at 186 MHz in the VHF band and capable of continuous wave operation while still delivering the high accelerating fields at the cathode required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…A detailed description of the VHF-Gun and of its characteristics can be found elsewhere [21,22], here, for the reader convenience, only the main relevant features of the gun are summarized. In the VHF-Gun scheme, the electron bunches are generated by laser-induced photoemission on high quantum efficiency (QE) semiconductor cathodes [24,29].…”
Section: The Vhf-gun and Apex The Advanced Photo-injector Experimentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the VHF-Gun and of its characteristics can be found elsewhere [21,22], here, for the reader convenience, only the main relevant features of the gun are summarized. In the VHF-Gun scheme, the electron bunches are generated by laser-induced photoemission on high quantum efficiency (QE) semiconductor cathodes [24,29].…”
Section: The Vhf-gun and Apex The Advanced Photo-injector Experimentioning
confidence: 99%
“…A review and description of these different schemes can be found elsewhere [19]. Our group at the Lawrence Berkeley National Laboratory (LBNL) took a different route developing the very-high-frequency gun (VHF-Gun), a novelscheme lower-frequency room-temperature RF photo-gun [20][21][22][23][24] capable of continuous wave (CW) operation and optimized for the performance required by MHz-class Xray FELs [25,26]. The Advanced Photo-injector EXperiment (APEX), an injector test facility, was built at LBNL for demonstrating the VHF-Gun performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although the DC gun showed good performances, for our purpose, to drive an X-ray FEL, the RF gun with a highest cathode electric field peak and a highest beam energy at the exit was preferable. Therefore, the gun presented in this work is a VHF RF gun like the APEX-I [6], working with a Cs 2 Te phothocathode [7][8][9], driven by an Yb:Yag IV harmonic laser pulse (257.5 nm), at 1 MHz rep rate.…”
Section: Machine Layoutmentioning
confidence: 99%
“…1. Table I shows the gun main parameters while a detailed description of the gun fabrication can be found in [13]. After the completion of the beam tests that demonstrated beams with the characteristics required to operate a high repetition rate FEL [6], the APEX VHF gun is now used at LBNL as the source for high repetition rate UED experiments in the framework of the HiRES project [14].…”
Section: Characteristics Of the Vhf-gun Schemementioning
confidence: 99%
“…The tuner system was also modified to extend (double) the range of tunability of the cavity frequency. Other minor modifications were implemented and are described in more detail in [13].…”
Section: Characteristics Of the Vhf-gun Schemementioning
confidence: 99%